Ragged Men on the Move: Poverty, Inertia and Friendship in Latife Tekin’s Swords of Ice (1989/tr.2007) - Karabag, Ayse Irem (Pivot: A Journal of Interdisciplinary Studies and Thought, 2022)
Latife Tekin’s Swords of Ice (1989/tr.2007) depicts the lives of Halilhan and his best friend Gogi, “ragged men” from Istanbul’s “outer most belt” (18). Smart, spiritual, and naïve, Gogi tries to help Halilhan, although Halilhan tricks his brothers and misuses company funds to buy a second-hand red Volvo. While the Volvo is the techne for upward mobility, power and status, Halilhan recognizes that his well-tuned friendship with Gogi is vital to escape the poverty that their neighborhood imposes. This paper analyzes the friendship between Gogi and Halilhan, as they mark a fragile transgression of territorial boundaries, class norms, and socio-political values.